Uncovering Ronald Tannur's Acquittal: Circumstantial Evidence as a Starting Point for Reforming Criminal Evidence System - Ladro Kusworo, Daffa (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The acquittal of Ronald Tannur sparked a polemic due to the dismissal of the combined charges filed by the Public Prosecutor. The judge's consideration that acquitted the defendant of all charges was based on the fact that when the incident took place there were no witnesses or CCTV footage proving that the defendant's actions resulted in the loss of the victim's life. Apart from violations of the code of ethics by judges, the Panel of Judges should be able to use circumstantial evidence as in Decision Number. 777/Pid.B/2016/Pn.Jkt.Pst Jessica Mirna case. Thus, based on this momentum, there is a need for the legality of circumstantial evidence as a reform of the criminal evidence system in Indonesia. This research method uses a doctrinal approach that refers to applicable laws and regulations and conceptual accompanied by literature studies in the form of books, journals, and other literature. The results showed that circumstancial evidence is nothing but evidence that assesses indirect evidence that does not stand alone, but is based on concrete legal facts and is linked to the sharpness of analysis and conscience of the Panel of Judges. However, the Criminal Procedure Code has never based the use of circumstantial evidence, so it should be a question of how judges can declare the existence of indirect evidence as something that is valid and can be commonly used when litigating. Based on the principle of legality, it is possible that the defendant Jessica could not be found guilty because the doctrine of such evidence has never been recognized in Indonesian legal institutions, especially in statutory regulations. Conversely, Ronald Tannur's acquittal could have been interpreted as in accordance with the corridors of the law because the use of the evidentiary system was in accordance with the technical procedural law. The judge may be said to have crossed the line of demarcation from what should be enshrined in the law because it contradicts Article 183 jo. 184 Paragraph (1) KUHAP because there were no direct witnesses who actually saw the murder committed